Relação entre sistema de cuidado, suporte social e fragilidade de idosos cuidadores - Rossetti, Estefani Serafim (2016)
Population aging is a global phenomenon related to changes in family structures and functions that bring consequences to the elderly, such as: change in living conditions, challenges in the care and social support, among others. This study aims to analyze the relationship between care system, social support and the fragility of senior caregivers in the context of high social vulnerability. It is an exploratory and analytical study, using the quantitative method of investigation. The population analyzed consisted of people aged 60 or over, who takes care of the seniors and were registered in the ”Unidades de Saúde da Família” (Public Family Health Units) in a city in the state of São Paulo and who are under the care of “ Núcleo de Apoio a Saúde da Família (NASF)” (Center for Support for Family Health), in the region of ARES “Cidade Aracy” (Aracy City). Interviews were conducted in the homes of elderly caregivers and used the following instruments for data collection: Semi-Structured Interviews, The Addenbrooke's Cognitive Examination Revised (ACE R), Geriatric Depression Scale (GDS), Fragility Assessment according to phenotype Fried, family APGAR, Genogram and ecomap. Most of the caregivers are spouses (83.6%), carefully time 1-4 years (46.5%) and spending one to four hours taking care (52%) of the elderly. The most mentioned institution that assists these seniors was a health institution. The main care provided to the elderly was feeding (82.2%), followed by lead to medical appointments (63.6%). There was a statistically significant association of low-income seniors with worse cognitive performance and the negative influence of the largest number of people living at home with worse results in cognition test. It is necessary to investigate the profile of these caregivers, as most are pre-fragile, and takes care of another pre-fragile elderly. It is noteworthy that the vast majority of the elderly in this study lives in houses with a large number of people, which is common in the context of high social vulnerability and low education; it was found that this factor interferes in the cognitive performance. More studies are necessary in order to investigate the conditions offered by the society and what these seniors, families and their social network can do in favor of a healthy aging.